Modalities and Effects of Left Ventricle Unloading on Extracorporeal Life support: a Review of the Current Literature. (May 2017) - Meani, Paolo; Gelsomino, Sandro; Natour, Eshan; Johnson, Daniel M; Rocca, Hans‐Peter Brunner La; Pappalardo, Federico; Bidar, Elham; Makhoul, Maged; Raffa, Giuseppe; Heuts, Samuel; Lozekoot, Pieter; Kats, Suzanne; et al.
Abstract: Introduction/Aim: Veno‐arterial extracorporeal membrane oxygenation (V‐A ECMO) support is increasingly used in refractory cardiogenic shock and cardiac arrest, but is characterized by a rise in afterload of the left ventricle (LV) which may ultimately either further impair or delay cardiac contractility improvement. The aim of this study was to provide a comprehensive overview regarding the different LV venting techniques and results currently available in the literature. Methods: A systematic literature search was performed in the PubMed database: 207 articles published between 1993 and 2016 were included. Papers dealing with pre‐clinical studies, overlapping series, and association with other assist devices were excluded from the review, with 45 published papers finally selected. Heterogeneous indications for LV unloading were reported. The selected literature was divided into subgroups, according to the location or the performed procedure for LV venting. Results: Case reports or case series accounted for 60% of the papers, while retrospective study represented 29% of them. Adult series were present in 67%, paediatric patients in 29%, and a mixed population in 4%. LV unloading was performed percutaneously in 84% of the cases. The most common locations of unloading was the left atrium (31%), followed by indirect unloading (intra‐aortic balloon pump) (27%), trans‐aortic (27%), LV (11%), and pulmonary artery (4%). Percutaneous trans‐septal approach was reported in 22%. Finally, the unloading was conducted surgically in 16%, with open chest surgery in 71%, and minimally invasive surgery in 29% of surgical cases. Conclusion: Nowadays, only a few data are available about left heart unloading in V‐A ECMO support. Despite the well‐known controversy, IABP remains widely used in combination with V‐A ECMO. Percutaneous approaches utilizing unloading devices is becoming an increasingly used option. However, further studies are required to establish the optimal LV unloading method.